STUDY OF THE ROLE OF HDPE WASTE AS A MATRIX FOR COMPOSITES REINFORCED BY IVORY FIBER FOR AUTOMOTIVE PRODUCTS - Saloom Hilton Siahaan; Muktar Bahruddin Panjaitan; Maren Sius Girsang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Hybrid composites are composites composed of several matrices and fibers, where the fiber types are vertical fibers and random fibers. The materials used to make hybrid composites are HDPE waste and palm fiber. With variations in fiber and powder volume fractions of 70%: 30% 60%: 40% and 50%: 50%, with different fiber directions, namely vertical and random, specimen making and testing procedures refer to ASTM D 638 for tensile tests and ASTM D256-03 for impact tests. A study has been conducted on the effect of variations in volume fractions in hybrid composites on the mechanical properties of the composite. The tests carried out in this study were tensile tests and impact tests. The results of the tensile test showed the highest value of 16.588 MPa for the variation of the HDPE volume fraction of 70% fiber 30% vertical fiber direction and the lowest value was 8.2762 MPa for the variation of the HDPE volume fraction of 60% fiber 40% with random fiber direction. While for the impact test the highest value was 8.53 joules with the variation of the HDPE volume fraction of 60% fiber 40% vertical fiber direction and the lowest value was 4.53 joules with the variation of the volume fraction of 60% fiber 40% with random fiber direction. It was concluded that if using the unidirectional fiber direction (vertical) to make the specimen, it will have better strength and toughness values.